Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

RolyPoly

  • 3 years ago

Boolean algebra Show that F(x, y, z) = xy + xz + yz has the value 1 if and only if at least two of the variables x, y, and z have the value 1. How can I show that apart from drawing the truth table??

  • This Question is Closed
  1. anonymous
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    since this is completely symmetric in \(x, y, z\) you can work by cases

  2. anonymous
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    by which i mean without loss of generality you can say \(x=1,y=1, z=1\) and get it, or \(x=1,y=1,z=0\) and also get it

  3. anonymous
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    then for the "if" part, take \(x=1,y=0,z=0\) and show it is not true and also in the case \(x=y=z=0\)

  4. RolyPoly
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    But then, it would be similar to drawing the truth table...

  5. mathsmind
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    i have attached a file of the truth table but it is not uploading for a reason probably due to a file format, however, all the cases are valid apart from 0 or 0 or 0 of your and statments

    1 Attachment
  6. mathsmind
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    0 represents F, and 1 represents T

  7. hartnn
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    here's what we can do without using truth table. Double complement F , F = (xy+yz+xz) '' =[ (xy+yz+xz)']' now use De-morgan's law on (xy+yz+xz) ' what you get ?

  8. hartnn
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    where a' means complement of a

  9. RolyPoly
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    (xy + yz +xz)'' = [(xy + yz +xz)']' = [(xy)' (yz)' (xz)']' = [(x'+y') (z'+y') (x'+z') ]' = [ (x'z' + y'z' + x'y' + y') ( x'+z') ]' = [ x'z' + x'y'z' + x'y' + y'z' ]' = [x'z' + x'y' (z'+1) + y'z' ]' = (x'y' + x'z' + y'z')'

  10. hartnn
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    yes, with (x'y' + x'z' + y'z')' you can conclude that F has the value 1 if and only if at least two of the variables x, y, and z have the value 1.

  11. hartnn
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    because if say you have only x=1 then (x'y' + x'z' + y'z')' = (0+0+1)' = 0

  12. hartnn
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    so, atleast 2 variables have to be 1 to get (x'y' + x'z' + y'z')' =1

  13. RolyPoly
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    (Testing) x=1, y=1 (x'y' + x'z' + y'z')' = (0 + 0 + 0)' = 1 x=1, z=1 (x'y' + x'z' + y'z')' = (0 + 0 +0)' = 1 y=1, z=1 (x'y' + x'z' + y'z')' = (0 + 0 + 0)' = 1 x=y=z=1 (x'y' + x'z' + y'z')' = (0 + 0+ 0)' =1 Wow!! Thanks!!!

  14. hartnn
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    welcome ^_^

  15. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy